Prospective Study of Different Staple Diets of Diabetic Indian Population. Issue 3 (July 2021) - Raghuram, Nagarathna; Anand, Akshay; Mathur, Deepali; Patil, Suchitra S.; Singh, Amit; Rajesh, S. K.; Hari, Geetharani; Verma, Prashant; Nanda, Sapna; Hongasandra, Nagendra
Background: Diabetes is a metabolic disorder characterized by chronic hyperglycemia. Its prevention and regulation depends on dietary pattern and lifestyle. There are numerous studies which have been conducted to elucidate the relationship between type of diet consumption and sugar levels. The objective of this study was to enumerate the distribution of the staple food consumed in seven zones across India and their association with sugar levels. Methods: A pan-India multicentered screening, covering the 63 districts, 29 states, and 4 union territories per populations, was undertaken. A specially designed questionnaire was administered for data collection, which comprised specific questions for diet 17, 280 sample was analyzed across seven zones of India. Statistical Package for the Social Sciences (SPSS; 21.0) software was used to analyze the data. Results: The survey suggested that rice and wheat are the major staple food consumed across different regions of India. In Jammu, North, East, South, and central zones, consumption of rice was more than wheat. However, in North and West zones, consumption of wheat was observed to be more than rice. Mean values of fasting blood sugar (FBS), postprandial blood sugar (PPBS) were high in the group consuming Bajra (128.3 & 160.5). Similarly, FBS mean was less in group consuming rice (114.6), and PPBS was low in group consuming ragi (149.2). Conclusion: Staple food has significant effect on FBS, PPBS and glycated haemoglobin cholesterol levels and anthropometric measurements.